Predictors of Radiologists' Perceived Risk of Malpractice Lawsuits in Breast Imaging - Dick, John F. (2009)
OBJECTIVE: The shortage of radiologists in breast imaging may be related to heightened malpractice lawsuit concerns. Our objective was to examine radiologists' reported experiences and perceptions of future lawsuit risk and explore personal and professional factors that may be associated with elevated perceptions of risk. MATERIALS AND METHODS: Radiologists who routinely interpret mammography examinations in diverse regions of the United States (Washington, Colorado, and New Hampshire) completed a mailed survey in 2002 and 2006, including questions on demographics, practice characteristics, and medicolegal experience and perceptions as well as a validated scale measuring reactions to uncertainty in clinical situations. A survey assessing the radiologists' work facilities was also completed in 2002. RESULTS: Participation by eligible radiologists was 77% (139 of 181) in 2002 and 71% (84 of 118) in 2006. The percentage of radiologists reporting malpractice claims related to mammography in the previous 5 years was 8% on the 2002 survey and 10% on the 2006 survey. Radiologists' mean estimate of the probability of being sued for malpractice in the next 5 years (41% in 2002 and 35% in 2006) was markedly higher than the actual reported risk. Radiologists' age, sex, clinical experience, and workload were not associated with a higher perceived risk of being sued. Radiologists who reported higher perceived risk of lawsuits were more likely to have experienced a prior malpractice claim, to report knowing colleagues with prior lawsuits, and to score higher on a scale measuring anxiety caused by uncertainty in clinical situations. Radiologists working at facilities that did not use double reading reported higher perceived risk, but the difference was not statistically significant. CONCLUSION: Radiologists working in breast imaging substantially overestimate their risk of a future malpractice lawsuit. Radiologists with higher risk perceptions show more negative reactions to uncertainty in a clinical setting. Understanding that their actual risk of malpractice lawsuits may be substantially lower than anticipated may help reduce radiologists' fears and alleviate the manpower shortage in mammography. Programs to address the shortage of breast imagers could be targeted toward radiologists with heightened malpractice lawsuit concerns.